2015
DOI: 10.1371/journal.pone.0121014
|View full text |Cite
|
Sign up to set email alerts
|

Is Scale-Up of Community Mobilisation among Sex Workers Really Possible in Complex Urban Environments? The Case of Mumbai, India

Abstract: BackgroundIn the last decade, community mobilisation (CM) interventions targeting female sex workers (FSWs) have been scaled-up in India’s national response to the HIV epidemic. This included the Bill and Melinda Gates Foundation’s Avahan programme which adopted a business approach to plan and manage implementation at scale. With the focus of evaluation efforts on measuring effectiveness and health impacts there has been little analysis thus far of the interaction of the CM interventions with the sex work indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…Programmatic recommendations to the EE settings are not so clear-cut, but there is a growing consensus that the interventions should be structural and targeting all key stakeholders, including the owners and management, for successful HIV/STI prevention [ 28 33 ]. In a study in the southern Philippines [ 28 ], female EE workers who received peer and establishment manager interventions, and establishment policies favouring condom use, reported more positive condom attitudes and fewer STIs than the peer-only intervention and the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Programmatic recommendations to the EE settings are not so clear-cut, but there is a growing consensus that the interventions should be structural and targeting all key stakeholders, including the owners and management, for successful HIV/STI prevention [ 28 33 ]. In a study in the southern Philippines [ 28 ], female EE workers who received peer and establishment manager interventions, and establishment policies favouring condom use, reported more positive condom attitudes and fewer STIs than the peer-only intervention and the control group.…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that the recommended programmatic actions tried in different settings did not necessarily produce good results all the time [ 32 ]. This was particularly so when stakeholder engagement was poor, for example in the case when owners and pimps obstructed such preventive interventions to the sex workers [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the lack of adequate funding is only one. Other explanations found in the literature include: institutional disbursement and policy constraints (Oomman, Nandini;Bernstein & Rosenzweig, 2007); difficulties involved in scaling up community-based projects (Binswanger-mkhize, Regt, & Spector, 2010); difficulties in operationalizing the concept of community mobilization in different contexts (Cornish et al, 2014;Kongelf, Bandewar, Bharat, & Collumbien, 2015;Mburu, Iorpenda, & Muwanga, 2012); and insufficient attention given to social and structural factors (Auerbach, Parkhurst, & Caceres, 2011).…”
Section: Implications For Community Responsesmentioning
confidence: 99%
“…Community mobilization programmes focus on bringing women together for participatory activities to build trust, strengthen social networks, and enhance both individual and collective agency in addressing structural determinants of their vulnerability to HIV [ 6 , 7 ]. Perhaps the best documented successes in community mobilization among female SWs come from India, where the well-renowned Sonagachi programme [ 8 , 9 ] has been replicated and scaled-up across six states in India through the Avahan initiative [ 10 , 11 ]. Avahan works to transform SWs’ role in health interventions from mere participants to social change agents with collective agency, ownership, and eventual sustainability of local organisations [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even within Avahan, some settings present greater challenges to the mobilization process than others. A qualitative study examining Avahan’s specific experience in Mumbai found that a much more challenging context for establishing an enabling environment for SWs’ collective action [ 11 ]. Greater control over SWs by brokers and pimps, and a fragmented, mobile and heterogeneous SW population weakened potential for women to come together and organise for mutual gain.…”
Section: Introductionmentioning
confidence: 99%